Investigation of Solid Dispersion Technique in Improvement ofPhysicochemical Characteristics of Ibuprofen Powder: Ibuptofen physicochemical characteristics - Mohammad Ali, Dabbagh; Taghipour, Behzad (Iranian Journal of Pharmaceutical Sciences, 2007)
Ibuprofen solid dispersions were prepared by the solvent and fusion-solventmethods using polyethylene glycol (PEG), polyvinylpyrrolidone (PVP), eudragit RSPO, eudragit RLPO and hydroxypropylmethylcellulose (HPMC) as carriers toimprove physicochemical characteristics of ibuprofen. The prepared solid dispersionswere evaluated for the flowability, solubility characteristics and dissolution behavior.Flowability studies of powders showed that solid dispersion technique improve flowproperties compared with the physical mixtures. Solid dispersion technique foundto be effective in increasing the aqueous solubility of ibuprofen. The dissolution ofibuprofen and polymers (PVP, HPMC, eudruagit and PEG-6000) were investigatedusing UVspectroscopy. Dissolution was carried out in phosphate buffer (pH 6.8)using a standard USPII dissolution apparatus. In vitrodissolution studies showedthat in the dispersion systems containing eudragit or HPMC, dissolution of ibuprofenwas retarded, which attributed to ionic interaction and gel forming, respectively. Butsolid dispersion containing PEG, as a carrier, gave faster dissolution rates than thephysical mixtures. Finally, solid dispersion of ibuprofen:PEG 6000 prepared in 1:1.5ratio showed excellent physicochemical characteristics and was found to be describedby the zero order kinetic, and was selected as the best formulation in this study.